Neurogenic thoracic outlet syndrome in division 1 collegiate athletes: Presentation, diagnosis, and treatment - Olson, E. M.; Dyrek, P.; Harris, T.; Fereydooni, A.; Lee, J. T.; Kussman, A.; Roh, E. (Clinical Journal of Sport Medicine, 2023)
Objective: Athletes who engage in repetitive upper-extremity exercise are susceptible to neurogenic thoracic outlet syndrome (nTOS). We sought to identify typical presenting symptoms and common findings on diagnostic workup, in addition to evaluating rates of return to play following various treatment interventions.